PELAKSANAAN PROMOSI MUSEUM LINGGAM CAHAYA DI KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU - Masyrifah, Syarifah; Arief, Andi M Rifiyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Linggam Cahaya Museum is the only one in Lingga regency. The purpose of this research is to know the implementation of promotion of Linggam Cahaya Museum in Lingga Regency, to know the parties who carry out promotion at Linggam Cahaya Museum, and to know what efforts are done in increasing tourist visit.This research uses qualitative method with descriptive approach. The subject of the research is the manager of Linggam Cahaya Museum Lingga Regency, Section Head of Promotion Facilities, Information and Cooperation of Tourism Department of Tourism, Youth and Sports of Lingga Regency, and the community. The data collection is done by observation, interview and documentation. Data analysis used in this research through data reduction stages, data presentation and conclusion.The results of this study concluded that the parties concerned to promote through advertising, personal selling, publicity, sales promotion, and digital marketing. The promoting party is the manager of the Linggam Cahaya museum Lingga Regency, the Lingga Regency Tourism, Youth and Sports Office, and the community. Efforts made in increasing tourist visits by providing visitor service and make better planning one of them in doing promotion.Key word : advertising, personal selling, publicity, sales promotion, and digital marketing